PENENTUAN KENAIKAN JABATAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS DAN PROFILE MATCHING Studi Kasus Kementerian Agraria Dan Tata Ruang/Badan Pertanahan Nasional - Andi Rukmana; Rusdah . (Universitas Insan Pembangunan Indonesia, 2021)
The problems that occur are subjective assessments in determining the election for promotion to officials of the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency, mistakes and difficulties in ranking positions in the selection and placement of positions that are not on target. It also caused jealousy among civil servants due to unclear results because so far they only used assessment results. The criteria used are Employee Work Objectives, Education, Training, Job History, and Assessment. This study is more focused on the purpose of knowing the effect of AHP on the weighted value generated by the Profile Matching method to reduce the level of subjectivity so that the results of determining promotions are faster, more accurate, and objective. The results of the calculation of the consistency ratio (CR) criteria for determining the position obtained the value = 0.039, the calculation result is less than ≤ 0.1 so that the comparison assessment criteria for determining promotion is consistent. The results of calculations using the AHP method and Profile Matching obtained the highest first value is Awaludin, S.H., M.H. value = 3.20, the second highest score is Drs. Imam Nawawi, M.Si, M.T. value = 3.12. In the calculation of 613 employees who were collected from 100 people who considered, the calculation value of AHP and Profile Matching 3.05 to 3.33 are attached in attachment 5.Keyword: Ministry, Assesment, SPK, AHP, Profile Matching, PNS, Subjective